Measurement of the isolated photon cross section in p over(p, ̄) collisions at sqrt(s) = 1.96 TeV - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Agelou, M; Agram, J; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; et al. (2006)
The cross section for the inclusive production of isolated photons has been measured in p over(p, ̄) collisions at sqrt(s) = 1.96   TeV with the DØ detector at the Fermilab Tevatron Collider. The photons span transverse momenta 23 to 300 GeV and have pseudorapidity | η | < 0.9. The cross section is compared with the results from two next-to-leading order perturbative QCD calculations. The theoretical predictions agree with the measurement within uncertainties. © 2006 Elsevier B.V. All rights reserved.